Prevalence and potency of trauma reminders 8.5 years after a terrorist attack - Kristin A. Glad; Kate Porcheret; Grete Dyb (European Journal of Psychotraumatology, 2023)
ABSTRACTBackground: Empirical knowledge about the prevalence and potency of reminders several years post-trauma, and how experiences with reminders relate to mental health and functioning, is scarce.Objective: The aim of this study was threefold: (1) systematically describe the type and frequency of trauma reminders experienced by survivors 8.5 years after a terrorist attack; (2) explore the intensity and duration of reactions evoked by various reminders; and (3) examine whether experiences with trauma reminders are associated with psychological distress and level of functioning almost a decade post-trauma.Method: 289 survivors (51.2% females, M age = 27.7, SD = 4.6) of the 2011 massacre on Utøya island, Norway, were interviewed 8.5 years post-terror. Participants were presented with a list of ten potential trauma reminders and asked to rate how frequently they had experienced each one in the past month, and the intensity and duration of the reactions evoked. Current posttraumatic reactions were measured using the UCLA PTSD-RI and the HSCL-8. Associations between experiences with reminders, psychological distress, and functioning, were analysed by linear regressions.Results: At 8.5 years post-terror, approximately 90% of the participants had experienced trauma reminders within the past month (35.6% often or very often). Almost 30% had become distressed, afraid, sad, or experienced bodily reactions to a great or very great extent. The vast majority reported that the reactions only lasted for a few minutes or hours. Frequency of exposure to reminders, and the intensity of the reactions evoked, were significantly associated with psychological distress. Frequency of exposure to trauma reminders was negatively related to the survivors’ level of functioning.Conclusions: Trauma reminders can still be a central source of psychological distress and impaired functioning among survivors almost a decade post-trauma. While everyone who is directly exposed to a terrorist attack does not need psychotherapy, most would probably benefit from psychoeducation about reminders.